KORPORASI DALAM PERSPEKTIF TINDAK PIDANA KORUPSI - Sihombing, Daniel Romi; Sihombing, Carens Agatha (Jurnal TEDC; Vol 20 No 1 (2026): JURNAL TEDCDO - 10.70428/tedc.v20i1.1496, 2026)
The development of corruption in Indonesia has transformed from individual crime to organized corporate crime, but the implementation of laws against business entities is still very limited despite being regulated in the Anti Corruption Law. This normative legal research shows that corporate criminal liability is based on the theories of vicarious liability, strict liability, and identification theory, where Article 20 of the Anti-Corruption Law allows for the prosecution of executives, corporations, or both. However, law enforcement faces serious obstacles, ranging from  unclear sanctions (legal), difficulties in proving cases and the conventional paradigm of the authorities (practice), to concerns about the economic impact (cultural). To overcome these challenges, this study recommends reformulating regulations to clarify criminal criteria and expand the types of sanctions, as well as strengthening the capacity of law enforcement through specialized units and forensic technology to create more effective and integrated corporate corruption eradication in Indonesia.